COLOR AND SIZE SORTING SYSTEM WITH AN ESP32-BASED ROBOT ARM - Adiguna, Muhamad Gilang Satria; Saleh, Muhammad; Marindani, Elang Derdian (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2023)
Robotics has seen an explosive increase in usage in the past few decades owing to its abundance of benefits and automation capabilities. The use of robotics is especially prominent in industries where the demand for precise and automatic robots in order to increase production efficiency is high. One of the robots commonly used in these industries is the arm robot model, which is a machine designed specifically to mimic some of the human arm’s capabilities in order to execute certain tasks over and over again, either autonomously or not. This paper will discuss the design of a robotic arm with five degrees of freedom capable of picking up and placing objects with three different colors and sorting the objects based on their size, starting from the largest to the smallest. The inclusion of an additional degree of freedom allows the robot to adjust the rotation of its grip to properly grab rotated objects. With an ESP32-CAM acting as its eyes, the robot is aided by a Python program run remotely on a separate Laptop in order to analyze video stream uploaded by the camera to determine the coordinates, color, size, and rotation of objects placed within the Detection Zone. The implementation of inverse kinematics equations run on an ESP32 microcontroller allows the robot to reach arbitrary coordinates specified by the Python program. Testing revealed that the resulting robot is able to perform the tasks it was designed to, namely recognizing and sorting colored boxes of different colors and sizes, with an accuracy 100% in recognition tasks and an accuracy of 91.5% in sorting tasks.